The effects of environmental performance, financial leverage, and institutional ownership on firm value: a study on manufacturing firms in Indonesia - Arfazil, Martha; Saputra, Mulia; Indayani (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2021)
This study aims to examine the relationships between environmental performance, financial leverage, as well as institutional ownership and firm value. In this study, firm value is measured with Tobin's Q ratio. The sample used in this study was 20 manufacturing firms listed at the Indonesia Stock Exchange with the observation period between 2016-2019; so, the total observations made were 80. Multiple regression analysis using SPSS application was carried out to scrutinize the data. The results of this study indicate that all independent variables tested, namely environmental performance, financial leverage, and institutional ownership, have positive influences on firm value. These results provide a good signal for the investors to continuously invest in manufacturing firms. In addition, good environmental performance has an impact on firms’ positive image.